Тепловая машина на вращающихся фуллеренах - Носырев, Олег Дмитриевич (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
The heat engine on rotating fullerenes is considered. The working body follows Carnot cycle in the coordinate angular momentum - angular velocity. A numerical experiment is carried out to demonstrate the part working cycle. The conclusion is made about the prospects of creating thermal machines based on chiral effects.